Isoform‐resolved correlation analysis between mRNA abundance regulation and protein level degradation. Issue 3 (16th March 2020) - Salovska, Barbora; Zhu, Hongwen; Gandhi, Tejas; Frank, Max; Li, Wenxue; Rosenberger, George; Wu, Chongde; Germain, Pierre‐Luc; Zhou, Hu; Hodny, Zdenek; Reiter, Lukas; Liu, Yansheng
Abstract: Profiling of biological relationships between different molecular layers dissects regulatory mechanisms that ultimately determine cellular function. To thoroughly assess the role of protein post‐translational turnover, we devised a strategy combining pulse stable isotope‐labeled amino acids in cells (pSILAC), data‐independent acquisition mass spectrometry (DIA‐MS), and a novel data analysis framework that resolves protein degradation rate on the level of mRNA alternative splicing isoforms and isoform groups. We demonstrated our approach by the genome‐wide correlation analysis between mRNA amounts and protein degradation across different strains of HeLa cells that harbor a high grade of gene dosage variation. The dataset revealed that specific biological processes, cellular organelles, spatial compartments of organelles, and individual protein isoforms of the same genes could have distinctive degradation rate. The protein degradation diversity thus dissects the corresponding buffering or concerting protein turnover control across cancer cell lines. The data further indicate that specific mRNA splicing events such as intron retention significantly impact the protein abundance levels. Our findings support the tight association between transcriptome variability and proteostasis and provide a methodological foundation for studying functional protein degradation. Synopsis: This study analyzes the gene isoform‐specific relationships between mRNA variation and protein degradation and underscores the diversity of protein turnover control in steady‐state gene expression. An optimized experimental and bioinformatic workflow is developed to study protein turnover in high throughput by combining single‐shot Data independent acquisition mass spectrometry (DIA‐MS) and pulse‐chase SILAC labeling experiments. The genome‐wide, protein specific correlation between mRNA variation and protein degradation is a powerful measure of post‐translational control in determining protein variability. The correlation analysis reveals the diversity of protein turnover at various scales, ranging from specific biological processes and organelles to sub‐organelles and splicing isoforms. mRNA intron retention switching mostly impacts the corresponding protein abundance but not protein degradation. Abstract : This study analyzes the gene isoform‐specific relationships between mRNA variation and protein degradation and underscores the diversity of protein turnover control in steady‐state gene expression.